A LysR-Type Transcriptional Regulator LcrX Is Involved in Virulence, Biofilm Formation, Swimming Motility, Siderophore Secretion, and Growth in Sugar Sources in Xanthomonas axonopodis Pv. glycines - Park, Hanbi; Do, Eunsoo; Kim, Minyoung; Park, Hye-Jee; Lee, Jongchan; Han, Sang-Wook (Frontiers in Plant Science, 2020)
Xanthomonas axonopodis pv. glycines (Xag) is a Gram-negative bacterium that causes bacterial pustule disease in soybean. To acclimate to new environments, the expression of genes in bacteria is controlled directly or indirectly by diverse transcriptional factors. Among them, LysR type transcriptional regulators are well-characterized and abundant in bacteria. In a previous study, comparative proteomic analysis revealed that LysR type carbohydrate-related transcriptional regulator in Xag (LcrX) was more abundant in XVM2, which is a minimal medium, compared with a rich medium. However, the functions of LcrX in Xag have not been characterized. In this study, we generated an LcrX-overexpressing strain, Xag(LcrX), and the knockout mutant strain, XagΔlcrX(EV), to elucidate the functions of LcrX. Bacterial multiplication of Xag(LcrX) in soybean was significantly impaired, indicating that LcrX is related to virulence. Comparative proteomic analysis revealed that LcrX is mainly involved in carbohydrate metabolism/transport and inorganic ion transport/metabolism. Based on the results of proteomics analysis, diverse phenotypic assays were carried out. A gel electrophoresis mobility shift assay demonstrated that LcrX specifically bound to the putative promoter regions of genes encoding putative fructose 1,6-bisphosphatase and protease. Through a 96-well plate assay under various conditions, we confirmed that the growth of Xag(LcrX) was dramatically affected in the presence of various carbon sources, while the growth of XagΔlcrX(EV) was only slightly changed. Biofilm formation activity was reduced in Xag(LcrX) but enhanced in XagΔlcrX(EV). The production of siderophores was also decreased in Xag(LcrX) but not altered in XagΔlcrX(EV). In contrast, LcrX was not associated with exopolysaccharide production, protease activity, or bacterial motility. These findings provide new insights into the functions of a carbohydrate-related transcriptional regulator in Xag.